2017
DOI: 10.31234/osf.io/8pjp9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leaning to the left makes the Eiffel tower seem smaller: Posture-modulated estimation

Abstract: In two experiments, we investigated whether body posture influences people’s estimation of quantities. According to the mental-number-line theory, people mentally represent numbers along a line with smaller numbers on the left and larger numbers on the right. We hypothesized that surreptitiously making people lean to the right or to the left would affect their quantitative estimates. Participants answered estimation questions while standing on a Wii Balance Board. Posture was manipulated within subjects so tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…In these paradigms, the participants are asked to provide random numbers from a specified number range (random number generation—RNG task) or provide estimates of some numerical values and execute some motor actions. It was shown that when people move their head (Loetscher, Schwarz, Schubiger, & Brugger, ), they walk (Shaki & Fischer, ) or lean in certain directions (Eerland, Guadalupe, & Zwaan, )—the direction of such movement strongly affects RNG or numerical estimation. Importantly, these associations are bidirectional—RNG influences motion direction (i.e., leftward/rightward turns are more likely after a small/large magnitude random number was generated) as well as motion direction influences RNG (i.e., generating small/large random numbers is more likely after leftward/rightward turns; Shaki & Fischer, ).…”
Section: Main Types Of Snas and Their Relation To Arithmetic Skillsmentioning
confidence: 99%
“…In these paradigms, the participants are asked to provide random numbers from a specified number range (random number generation—RNG task) or provide estimates of some numerical values and execute some motor actions. It was shown that when people move their head (Loetscher, Schwarz, Schubiger, & Brugger, ), they walk (Shaki & Fischer, ) or lean in certain directions (Eerland, Guadalupe, & Zwaan, )—the direction of such movement strongly affects RNG or numerical estimation. Importantly, these associations are bidirectional—RNG influences motion direction (i.e., leftward/rightward turns are more likely after a small/large magnitude random number was generated) as well as motion direction influences RNG (i.e., generating small/large random numbers is more likely after leftward/rightward turns; Shaki & Fischer, ).…”
Section: Main Types Of Snas and Their Relation To Arithmetic Skillsmentioning
confidence: 99%
“…Rather, DST behavioral analysis suggests that changes in motor components at two different timescales affected behavioral change: reaches made over the course of an experiment and motor stability over the course of development. Thus, this work demonstrates that the behavior is not just about cognitive‐level processes but about the body as well—the representation of things in the world is tightly coupled to the dynamics of the body (see also Eerland, Guadalupe, & Zwaan, ; Zwaan & Kaschak, for related results in adults; and Zwaan, van der Stoep, Guadalupe, & Bouwmeester, for discussion). This has been recently demonstrated by instantiating the DNF model in an autonomous robot and quantitatively simulating experimental data from infants (Schöner et al., in press).…”
Section: The A‐not‐b Errormentioning
confidence: 69%
“…Indeed it is fairly easy to collect respected academic publications guided by data analysis in which their authors acknowledge a lack of understanding in front of strong observed associations among diverse pieces of data. Illustrative examples are: a country can increase its Nobel laureates by stimulating chocolate consumption (Messerli, ); large climate variations increase conflict around the world (Hsiang et al , ); cat bites might cause depression (Hanauer et al , ); leaning to the left makes the Eiffel Tower seem smaller (Eerland et al , ). The problem of induction should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%